Clinical management and research priorities for high-risk prostate cancer in the UK: Meeting report of a multidisciplinary panel in conjunction with the NCRI Prostate Cancer Clinical Studies Localised Subgroup. (November 2016) - Gnanapragasam, VJ; Hori, S; Johnston, T; Smith, D; Muir, K; ,; Alonzi, R; Winkler, M; Warren, A; Staffurth, J; Khoo, V; Tree, A; et al.
The management of high-risk prostate cancer has become increasingly sophisticated, with refinements in radical therapy and the inclusion of adjuvant local and systemic therapies. Despite this, high-risk prostate cancer continues to have significant treatment failure rates, with progression to metastasis, castrate resistance and ultimately disease-specific death. In an effort to discuss the challenges in this field, the UK National Clinical Research Institute's Prostate Cancer Clinical Studies localised subgroup convened a multidisciplinary national meeting in the autumn of 2014. The remit of the meeting was to debate and reach a consensus on the key clinical and research challenges in high-risk prostate cancer and to identify themes that the UK would be best placed to pursue to help improve outcomes. This report presents the outcome of those discussions and the key recommendations for future research in this highly heterogeneous disease entity.